Construction Aspects of System for Wireless Low Power Transfer on Moving Parts of Electric Machinery - Kindl, Vladimir; Kavalir, Tomas; Pechanek, Roman (Communications - Scientific letters of the University of Zilina, 2015)
The paper discuses important construction aspects of resonant wireless power transfer (WPT) system for moving parts of electric machinery. It focuses mainly on key electrical parameters of the systems resonant linkage and its simple and durable construction shape. All presented theoretical presumptions are consequently verified by detailed measurement.